History MYP by concept 4&5 - Rogers, Keely; Thomas, Jo (MYP by concept, 2015)
The MYP (Middle Years Programme) is a challenging framework that encourages students to make practical connections between their studies and the real world. The resources drive meaningful inquiry through unique concept-driven narratives and support every aspect of assessment. MYP by concept 4&5 are the only resources developed with the IB (International Baccalaureate).